Extending the operating region of inductive power transfer systems through dual-side cooperative control - Chen, Shuxin (2022)
A wide operating region of inductive power transfer systems indicates a stable output against large load and coupling changes. In most of the published works, output regulation is achieved by single-side regulation that utilizes either primary-side or secondary-side power converters for load regulation. However, secondary-side regulation tends to have a relatively narrow operating region due to space and cost considerations. Meanwhile, although primary-side regulation may provide a larger operating region, system performance can be degraded due to the needs of secondary-side information. To overcome the drawbacks of single-side regulation, this article proposes a dual-side cooperative output regulation method implemented by burst-mode pulse density modulation. In the proposed method, dual-side cooperative control is established by sensing primary-side current drops caused by secondary-side burst operations and, hence, requires no communication devices. With the proposed method, the system operating region can be effectively extended without sacrificing steady-state performance. Experimental results are provided in this article to validate the proposed method.